Proton exchanged waveguides in LiNbO3: Characterization and design methodology - Leite, António Manuel Pais Pereira (2006)
The purpose of this work was to develop a design methodology for the fabrication of proton exchanged channel waveguides in LiNb03 operating in the singlemode regime at several wavelengths, with specific characteristics required to optimize integrated devices. To achieve this, it is necessary to obtain the relations between the optical characteristics of the waveguides and their respective fabrication conditions, and to introduce models of the waveguide formation process. The relations between fabrication conditions and optical characteristics of planar waveguides realized by proton exchange in benzoic acid are documented extensively in the literature. However, reports on the characterization of waveguide fabrication processes, performed in a systematic way, could not be found, resulting in the need to combine information from several sources. Discrepancies among results from different researches are evident, resulting from different experimental methodologies and calibration of equipment. Therefore, aiming at extracting a consistent data set, optical characterization techniques of the refractive index profile were employed to study series of samples.